The Moderating Role of Learning Environment in Self-Efficacy, Learning Motivation, and Academic Achievement Relationship - Ratna Juita; Almasdi Syahza; Suarman Suarman (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to examine the effect of self-efficacy and learning motivation on academic achievement with the learning environment as a moderating variable. The research approach used is quantitative, with a questionnaire as the main instrument. A total of 114 Economics Education students at Syarif Kasim Riau State Islamic University were selected using a stratified random sampling technique. The collected data were analyzed using descriptive quantitative techniques, followed by classical assumption tests and Moderated Regression Analysis (MRA) to assess the effect before and after the inclusion of moderating variables. The results showed that self-efficacy has a significant effect on student academic achievement. Similarly, learning motivation has a significant influence on academic achievement. In addition, the learning environment acts as a moderating variable that strengthens the relationship between self-efficacy, learning motivation, and academic achievement. It shows that a conducive learning environment can increase self-efficacy and have a positive impact on academic achievement. In addition, a supportive and productive learning environment can increase learning motivation, encouraging enthusiasm to achieve better academic results.